Formation of Anticoagulants by Digesting Fibrin with Thrombin - Triantaphyllopoulos, D. C; Muirhead, C. R (Thrombosis and Haemostasis, 1968)
Purified thrombin was able to digest fibrin clots in the combined presence of ε-ACA and Trasylol. The digestion products prolonged the thrombin clotting time of both fibrinogen and plasma and inhibited completely the coagulation of shed blood. The incidental observation was made that phosphate buffer elutes from Amberlite IRC-50 a nondialyzable anticoagulant which can easily be neutralized by calcium salts.